Analisa Strategi Pemasaran Untuk Meningkatkan Penjualan Produk Pada Industri Mebel â€œTâ€ Desa Poka Kecamatan Teluk Ambon Provinsi Maluku - Wa Emi Nurlette; Sherly Rutumalessy; Gilbert Alvin Rumalatu (Jurnal Administrasi Terapan, 2024)
The furniture industry is a type of business whose products can be marketed and are able to compete in the world of market competition. And that is what happened to "T" furniture in Poka Village, Teluk Ambon District, Maluku Province, which produces goods based on orders. However, what happened to "T" furniture was that the marketing strategy implemented was less than optimal and had an impact on sales results that did not meet sales targets, as a result of implementing a marketing strategy through a marketing mix that was not yet effective. The aim of this research is to analyze the marketing strategy applied to "T" furniture.The method used is a qualitative method consisting of marketing mix indicators such as product strategy, distribution strategy, promotion strategy and pricing strategy and the research technique used is through interviews, observation and documentation, then analysis is carried out using a literature study approach and then described using a descriptive qualitative approach. The research results show that "T" furniture has not been able to implement the marketing mix strategy optimally.In reality, what happens is that the marketing strategy implemented does not have much influence on production marketing because its implementation is not optimal. For this reason, "T" furniture must implement a marketing strategy through a good and appropriate marketing mix in order to achieve sales targets and attract consumer buying interest. Keywords: Marketing strategy